Effect of intracuff alkalinised lidocaine alone and combined with dexamethasone on post-extubation emergence in smokers undergoing elective surgeries under general anaesthesia - Sumeera Fayaz; Raja Suhail Shounthoo; Rohey Jan; Ajaiz Rasool; Altaf Hussain Mir; Majid Jahangeer; Showkat Ahmad Gurcoo (Asian Journal of Medical Sciences, 2025)
Background: Emergence phenomena (EP) following general anaesthesia (GA), such as cough, sore throat, and hoarseness, are common yet often overlooked. This study aimed to evaluate the effects of intracuff alkalinized lidocaine and dexamethasone in attenuating endotracheal tube (ETT)-induced EP. Aims and Objectives: The study aimed to assess the effect of intracuff alkalinized lidocaine, alkalinized lidocaine with dexamethasone, and saline on the occurrence and severity of post-operative cough, sore throat, and hoarseness in smokers for 24 h after surgery. In addition, it aimed to evaluate their efficacy in maintaining intracuff pressure and to assess hemodynamic changes during emergence from GA. Materials and Methods: This prospective, observational study included 90 American Standards Association II and III male patients aged 20–50 years with a 5-year smoking history. Patients were divided into three groups of 30 to receive either alkalinized lidocaine, alkalinized lidocaine with dexamethasone, or saline as the cuff inflation agent. Results: Cuff pressure increased in all groups (P>0.05). The cough was more severe and frequent in the saline group (P<0.05). Sore throat and hoarseness occurred less frequently in the alkalinized lidocaine and lidocaine-dexamethasone groups compared to the saline group, with less severity observed at 3 h- and 24-h post-extubation. Conclusion: Alkalinized lidocaine with dexamethasone for ETT cuff inflation was as effective as alkalinized lidocaine in reducing post-extubation symptoms and more effective than saline.